2010
DOI: 10.1109/tip.2010.2045702
|View full text |Cite
|
Sign up to set email alerts
|

Software Designs of Image Processing Tasks With Incremental Refinement of Computation

Abstract: We propose software designs that perform incremental computation with monotonic distortion reduction for twodimensional convolution and frame-by-frame block-matching tasks. In order to reduce the run time of the proposed designs, we combine bitplane-based computation with a packing technique proposed recently. In the case of block matching, we also utilize previously-computed motion vectors to perform localized search when incrementing the precision of the input video frames. The applicability of the proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…This can reduce the expected overhead when increasing the number of increment layers. In our recent work on software designs for incremental image processing [6], we found that three or four increment layers provide for sufficient quality-complexity scalability without significant overhead in the overall execution time. From the implementation perspective, a crucial element needed in order to take advantage of the reduction of the multiplication bitwidth is a multiplier unit with adjustable circuit activity according to the input bit patterns.…”
Section: B Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This can reduce the expected overhead when increasing the number of increment layers. In our recent work on software designs for incremental image processing [6], we found that three or four increment layers provide for sufficient quality-complexity scalability without significant overhead in the overall execution time. From the implementation perspective, a crucial element needed in order to take advantage of the reduction of the multiplication bitwidth is a multiplier unit with adjustable circuit activity according to the input bit patterns.…”
Section: B Discussionmentioning
confidence: 93%
“…However, since (19) and (20) involve two multiplications, this may not be cost-effective in comparison to (6).…”
Section: B Multilevel Extensionmentioning
confidence: 99%
See 1 more Smart Citation
“…ACKED linear image processing hinges on the idea that the dynamic range of a 32-bit or 64-bit numerical representation can be used for the concurrent calculation of multiple small-dynamic-range integer operations if the operands are positioned (or "packed") in such numerical representation with appropriate spacing from each other [1], [2]. This has been proposed for a variety of image processing operations such as bound estimation, image cross-correlation and orientation correlation [1], incremental image convolution and motion estimation [2], integer block-transform decomposition [3] and integer wavelet transforms [4].…”
mentioning
confidence: 99%
“…This has been proposed for a variety of image processing operations such as bound estimation, image cross-correlation and orientation correlation [1], incremental image convolution and motion estimation [2], integer block-transform decomposition [3] and integer wavelet transforms [4].…”
mentioning
confidence: 99%